KETAHANAN SEKTOR KEUANGAN DAN SHADOWBANKING: ANALISA TERHADAP INDUSTRI PEMBIAYAAN DI INDONESIA - Adriyanto, Adriyanto (Jurnal Kajian Ekonomi dan Keuangan, 2012)
The failure of supervision instrument on shadow banking practice in the US has triggered financial collapse and spread accross sovereignities. The G20 has asked FSB to undertake in depth analysis of shadow banking progress along with needed recommendations to overcome the weaknesses. This paper attempts to analyze the shadow banking practice in Indonesia particularly in the consumer finance industry by using the flow of fund analysis recommended by FSB and several relevant financial ratios. The size of credit intermediation in this industry only accounts for 3% of GDP compared to bank credit accounting for 30% of GDP in 2011, however the credit growth in finance industry has superseded banking sector. The consumer finance industry are dominantly reliant on bank lending and bond which reduces the susceptibility of market shock. The asset securitization is not common in this industry. The financial sector authority has imposed strick regulation on this industry to ensure industry's financial health. Despite industry's ability to meet those requirements, the high dependency on debt for operation has raised concern for stronger equity increase. Further, the expansive credit intermediation in this industry can bring liquidity problem which requires further regulation.